Analisis Keberlanjutan Taman Nasional Komodo sebagai Destinasi Wisata Berkelanjutan - Mariati, Sri; Parera, Adriana Klara; Rahmanita, Myrza (Jurnal Ilmiah Pariwisata; Vol 27 No 2 (2022): Jurnal Ilmiah Pariwisata, 2022)
Komodo National Park, designated by UNESCO as a world heritage site, is the only place where the ancient species of Komodo dragon (Varanus komodoensis) lives., its savanna panorama, and beautiful underwater scenery, attract both domestic and foreign tourists. This research was conducted to analyze the management system of Komodo National Park. To find out and analyze the perception of the government and the community towards the development of Komodo National Park tourism and analyze the sustainability of the current Komodo National Park tourism development. This research method uses the McKinsey and GSTC Criteria and Indicators (2019). The results of the study show that the current management system of Komodo National Park is still not good because it does not have adequate human resources and has not yet achieved a strategic management system. The results of our study indicate that the government's perception of information on the development of the Komodo tourism area is well understood so that it is coordinated effectively. Effectively, for destination sustainability in KNP, management results are 93% (very good), socio-economic sustainability is obtained 62.5% (good enough), cultural sustainability is 31% (poor), and environmental sustainability is 52.3% (good enough). Keywords: Management Komodo National Park, Sustainable Tourism